Genome-wide profiling of micro-RNA expression in gefitinib-resistant human lung adenocarcinoma using microarray for the identification of miR-149-5p modulation. Issue 3 (March 2017) - Hu, Yong; Qin, Xiaobing; Yan, Dali; Cao, Haixia; Zhou, Leilei; Fan, Fan; Zang, Jialan; Ni, Jie; Xu, Xiaoyue; Sha, Huanhuan; Liu, Siwen; Yu, Shaorong; et al.
To understand the mechanism involved in gefitinib resistance, we established gefitinib-resistant human HCC827/GR-8-1 cell line from the parental HCC827 cell line. We compared the micro-RNA expression profiles of the HCC827 cells HCC827/GR-8-1 using Agilent micro-RNA microarrays. The micro-RNAs, such as the miR-149-5p, were up- or downregulated and associated with acquired gefitinib resistance. Quantitative real-time polymerase chain reaction was then performed to verify the expression patterns of different micro-RNAs. The result showed that miR-149-5p was upregulated in the HCC827/GR-8-1 cell line. To investigate the biological function of miR-149-5p in non–small cell lung cancer cells acquired gefitinib resistance, we examined cell proliferation using a cell counting kit-8 assay. Cell viability was evaluated after the miR-149-5p mimics, inhibitors, and negative control were separately transfected into the non–small cell lung cancer cells. The results showed that the non–small cell lung cancer cells transfected with miR-149-5p mimics exhibited reduced cell motility. The drug-sensitivity assay results revealed that the overexpression of miR-149-5p effectively evaluates the half maximal inhibitory concentration values of the cell in response to gefitinib, and the downregulation of miR-149-5p can attenuate the half maximal inhibitory concentration values of the cell lines in response to gefitinib. Furthermore, the levels of miR-149-5p in the HCC827 and HCC827/GR-8-1 cells were inversely correlated with caspase-3 expression. In conclusion, this study revealed that miR-149-5p is upregulated in the HCC827/GR-8-1 cells and involved in the acquired gefitinib resistance.